Pengaruh Profitabilitas dan Solvabilitas Terhadap Yield Sukuk dengan Peringkat Sukuk Sebagai Variabel Moderator pada Perusahaan di Indonesia - Setiyani, Eprisa Risky; Baihaqi, Jadzil; Supriyadi, S. (IAIN Kudus, 2019)
This study aims to determine the effect of profitability and solvency on sukuk yields with Sukuk ratings as moderator variables. The population of this study is the company that issued Sukuk on the IDX in 2014-2017. By using a purposive sampling technique, there are 9 companies with 34 Sukuk as the final sample. This study uses a quantitative approach with secondary data types. The analysis technique uses multiple linear regression and Moderated Regression Analysis supported by IBM SPSS 24. The results are (1) Profitability does not have a significant effect on sukuk yield. This is because regardless of the company's profits, the investor still receives a refund and the fee specified. (2) Solvability has a significant positive effect on sukuk yield. (3) The sukuk rating is not able to moderate the relationship between profitability and sukuk yield. (4) Sukuk rating can moderate the solvency relationship with sukuk yield.